Theoretical and empirical contributions to the study of the organizational climate. a reflection in public organizations - Arévalo Ascanio, José Gregorio; Navarro Claro, Genny Torcoroma; Bayona Trillos, Ramón Armando (Universidad Francisco de Paula Santander, 2016)
The development of a good organizational climate in companies, has become a global concern, not only for its impact on the health of workers but also for its influence on the provision of good service and consequently in customer satisfaction,and the productivity of companies. Due to the above, in this article a reflection is made of the theoretical and empirical contributions of various authors on the development of the organizational climate in public institutions, resulting in a high consensus regarding the importance of studying the subject;post that allows to know the perceptions of managers and workers as well as identify strengths and weaknesses that directly affect the organization.